Histological, immunohistochemical and ultrastructural features of polyglucosan bodies in uterine smooth muscle of pet rabbits (Oryctolaguscuniculus). (February 2023) - Yoshimura, Hisashi; Torikai, Kazushi; Takahashi, Anna; Michishita, Masaki; Kishimoto, Takuya E; Yamamoto, Masami; Haritani, Makoto; Takahashi, Kimimasa; Kamiya, Shinji
Abstract: We document the frequency and morphological and immunohistochemical features of inclusion bodies in uterine smooth muscle cells in 56 (76%) of 74 investigated pet rabbits ( Oryctolagus cuniculus ). Inclusion bodies began to appear at the age of 2 years and their frequency increased with age ( P  = 0.047, r  = 0.33). They ranged from 5 to 20 μm in diameter, were slightly basophilic to amphophilic with well-delimited oval bodies in haematoxylin and eosin-stained tissue sections and formed in the cytoplasm of the uterine smooth muscle cells with displacement of the cell nuclei. The inclusion bodies were positive with periodic acid–Schiff, Best's carmine, Lugol's iodine and Grocott's methenamine silver methods. They were immunoreactive to a monoclonal antibody raised against human polyglucosan and negative with monoclonal antibodies for several intermediate filament proteins. Electron microscopy revealed that they were non-membranous structures composed of electron-dense amorphous material. The morphological, histochemical, immunohistochemical and ultrastructural features of the inclusion bodies in the rabbi uteri were similar to those of human polyglucosan bodies (PGBs). PGBs appear to occur at a high frequency in the uterus of rabbits, which are known to be susceptible to uterine diseases. Graphical abstract: Image 1